2002
DOI: 10.1002/jae.689
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical comparison between integrated and realized volatility

Abstract: SUMMARYIn this paper we provide both qualitative and quantitative measures of the precision of measuring integrated volatility by realized volatility for a fixed frequency of observation. We start by characterizing for a general diffusion the difference between realized and integrated volatility for a given frequency of observation. Then we compute the mean and variance of this noise and the correlation between the noise and the integrated volatility in the Eigenfunction Stochastic Volatility model of Meddahi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
201
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(205 citation statements)
references
References 35 publications
3
201
0
1
Order By: Relevance
“…A loss function, L, is ''robust'' if the ranking of any two (possibly imperfect) volatility forecasts, h 1t and h 2t , by expected loss is the same whether the ranking is done using the true conditional variance, σ 2 t , or some conditionally unbiased volatility proxy,σ 2 t . That is, Meddahi (2001) showed that the ranking of forecasts on the basis of the R 2 from the Mincer-Zarnowitz regression:…”
Section: Volatility Forecast Comparison Using An Imperfect Volatilitymentioning
confidence: 99%
“…A loss function, L, is ''robust'' if the ranking of any two (possibly imperfect) volatility forecasts, h 1t and h 2t , by expected loss is the same whether the ranking is done using the true conditional variance, σ 2 t , or some conditionally unbiased volatility proxy,σ 2 t . That is, Meddahi (2001) showed that the ranking of forecasts on the basis of the R 2 from the Mincer-Zarnowitz regression:…”
Section: Volatility Forecast Comparison Using An Imperfect Volatilitymentioning
confidence: 99%
“…and Barndorff-Nielsen and Shephard (2005b), Meddahi (2002), Gonçalves and Meddahi (2005), and Nielsen and Frederiksen (2006) studied the finite sample behavior of the limit theory given in (3). The main conclusion is that (3) is poorly sized, but…”
Section: The Distribution Of Rvmentioning
confidence: 99%
“…Based on the theoretical results of Barndorff-Nielsen and Shephard (2002), , and Meddahi (2002), several recent studies have documented the properties of realized volatilities constructed from high frequency data. However, as will be discussed later, microstructure effects introduce a severe bias on the daily volatility estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Meddahi (2002) proves that η t (∆) has a nonzero mean, when the drift in prices is non-zero, and is heteroskedastic. The correlation between IV and η t (∆) is zero when there is no leverage effect Shephard, 2002b andMeddahi, 2002).…”
Section: Estimation Of the Heston Model With Microstructure Noisementioning
confidence: 92%